The necessitive impersonal REIK(Ė)TI ‘need’: the rise of modal meaning - Jasionytė-Mikučionienė, Erika; Šinkūnienė, Jolanta (Lietuvių kalba, 2017)
The focus of the paper is on the frequency, distribution patterns and semantic profile of the necessitive impersonal reik(ė)ti ‘need’ in old and contemporary Lithuanian texts. The study employs corpus based quantitative and qualitative analysis to investigate the patterns of use of reik(ė)ti ‘need’ in the Database of Old Writings (16th-17th centuries) as well as the fiction sub-corpus of the Corpus of the Contemporary Lithuanian Language and the humanities and biomedical sciences sub-corpora of the Corpus of Academic Lithuanian (CorALit). The study follows van der Auwera and Plungian’s (1998) modality framework. The quantitative analysis shows that the present tense form reikia ‘need.PRS.3’ is the dominating one across all the sub-corpora analysed. The results of the qualitative study indicate that the deontic sub-type of participant external modality is prevailing in the old Lithuanian texts as well as in the fiction sub-corpus and in the biomedical sciences texts of the contemporary Lithuanian. The discourse of the humanities displays a fairly frequent employment of reik(ė)ti ‘need’ for discourse organising functions alongside the deontic uses. Although the usage patterns of reik(ė)ti ‘need’ in the biomedical sciences and the humanities share certain common features, they also point to discipline specific trends of argumentation. It is also important to observe that the objective deontic reik(ė)ti ‘need’ seems to gradually acquire the features of subjective deontic modality over time, which corresponds to the typical subjectification cline (cf. Traugott 1989).
Keywords: corpus-based study; quantitative and qualitative analysis; impersonal verb; modality; discourse function; subjectification